Analysis of digital literacy development to improve skills, competence, and self-confidence in students - Budi, Savitri Citra; Putri, Divi Galih Prasetyo (International Journal of Public Health Science (IJPHS), 2024)
Education is an essential aspect of human resource development. Additional learning facilities in the form of patient acceptance digital literacy are needed to improve students' skills and competencies before carrying out work practices. This study aimed to analyze the need for developing digital literacy in patient admission applications in health services. This investigation adopts a qualitative research methodology characterized by an exploratory perspective. Data gathering encompassed conducting interviews, observations, and reviewing documentary materials. Digital literacy patient acceptance of applications needs to be developed immediately to support the preparation for practical work activities. Things that need to be designed to create digital literacy are the function features provided, the display of the dashboard menu, and the material the participants must master. This research was successful in helping to collect the data needed to develop digital literacy in patient admission applications in health services. This research is expected to offer insights that can be valuable for future studies focused on enhancing digital literacy through characteristics, interfaces, and learning materials.